FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI DESA LIMAU ASRI (SP V) - Eni Setianingsih; Nely Salu Padang (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2018)
ENI SETIANINGSIH (302701141020040), Factors Affecting Rice Production in Limau Asri Village (SP V). Consultant (ABU BAKAR, SE., M.Sc). The aims of this research were to determine the effect of production factors (land, capital and labor) on the yield of rice production in Limau Asri Village (SP V) both simultaneously and partially. The approach used by researcher is an assositive approach which aims to determine the relationship between independent variables (land, capital and labor) and the dependent variable (production). The techniques of collection Data conducted by researchers were interviews and distributing questionnaires distributed to 8 respondents. The analytical tool used in this research is multiple linear regression analysis in the natural logarithm (ln) transformation Based on the results of the partial test research is done by testing the two-side curve by comparing between t count and t table. The value of t table obtained is 2.570 while the tcount for each factor of land production is -2.769, capital is 1.574 and labor is 7.425. From the tcount value, it is obtained the value of tcount ≥ t table, namely land and labor, while the capital production factor is tcount ttable. So that partially the use of production factors has no significant effect on the yield of rice production in Limau Asri Village (SP V). Thus the first hypothesis which states that the factors of production (land, capital and labor) have a partial effect on the yield of rice production in Limau Asri Village (SP V) is rejected. From the simultaneous test results obtained the value of Fcount ≥ Ftable is 24.409 ,5 6.59 so that H0 is rejected and H1 is accepted. Thus the first hypothesis that the factors of production (land, capital and labor) simultaneously have a significant effect on the yield of rice production in Limau Asri Village (SP V) is accepted.